Indian agriculture, air pollution, and public health in the age of COVID - McDonald, A.J.; Balwinder-Singh; Jat, M.L.; Craufurd, P.; Hellin, J.; Hung, N.V.; Keil, A.; Kishore, A.; Kumar, V.; McCarty, J.L.; Pearson, P.; Samaddar, A.; et al. (Elsevier, 2020)
Emerging evidence supports the intuitive link between chronic health conditions associated with air pollution and the vulnerability of individuals and communities to COVID-19. Poor air quality already imposes a highly significant public health burden in Northwest India, with pollution levels spiking to hazardous levels in November and early December when rice crop residues are burned. The urgency of curtailing the COVID-19 pandemic and mitigating a potential resurgence later in the year provides even more justification for accelerating efforts to dramatically reduce open agricultural burning in India.